Traceability Analysis and Control Measures of TVOC in Rail Passenger Vehicles - XIA Chunjing; ZHOU Dan; CHEN Guang (Chengshi guidao jiaotong yanjiu)
[Objective] The mass concentration and composition of TVOC (total volatile organic compounds) inside rail passenger vehicles are influenced by a combination of interior components and chemical products. Therefore, it is necessary to conduct traceability analysis and implement classified control measures for TVOC inside the vehicles. [Method] Taking a newly manufactured and fully equipped rail passenger vehicle as an example, the TVOC mass concentration and composition in each carriage, as well as in the interior materials, components, and chemical products (paints and adhesives), are tested and analyzed. A method for determining the main sources of TVOC inside the vehicle is clarified, and the components and chemical products that significantly affect the TVOC mass concentration and composition are further identified. [Result & Conclusion] The main types of TVOC-releasing substances and proportions of each substance are similar across different areas inside the rail passenger vehicle. However, there are significant differences of the TVOC mass concentration and component composition among the materials and components used inside the vehicle. The obtained TVOC mass concentrations of the chemical products used inside the vehicle under different testing methods are positively correlated. The main types of components and their proportion rankings are largely consis-tent, but with different release rates. Materials and components contribute a relatively small proportion to the overall TVOC mass concentration in the entire vehicle, accounting for only 12%. Chemical products have a significant impact on the TVOC mass concentration in the entire vehicle，and this impact degree depends comprehensively on the location and coverage state of the chemical products. Notably, adhesives used in direct exposure require focused control measures.